2005
DOI: 10.1002/chin.200546174
|View full text |Cite
|
Sign up to set email alerts
|

Newbouldiaquinone and Newbouldiamide: A New Naphthoquinone—Anthraquinone Coupled Pigment and a New Ceramide from Newbouldia laevis.

Abstract: For Abstract see ChemInform Abstract in Full Text.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
10
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 1 publication
0
10
0
1
Order By: Relevance
“…In addition, the antioxidant, antiulcerogenic, arginase inhibitory, hepatoprotective and antibacterial properties of the aqueous leaf extract have been reported [18,19,20,21]. Previous studies have shown that among compounds isolated from the Bignoniaceae, naphthoquinones in general and furanonaphthoquinones in particular, exhibit a broad spectrum of biological activities [22][23][24][25]26].…”
Section: Despitementioning
confidence: 99%
“…In addition, the antioxidant, antiulcerogenic, arginase inhibitory, hepatoprotective and antibacterial properties of the aqueous leaf extract have been reported [18,19,20,21]. Previous studies have shown that among compounds isolated from the Bignoniaceae, naphthoquinones in general and furanonaphthoquinones in particular, exhibit a broad spectrum of biological activities [22][23][24][25]26].…”
Section: Despitementioning
confidence: 99%
“…They are widely accepted as an important and promising alternative drug delivery system because they are endowed with several advantages of different traditional drug carrier systems, while avoiding some of their disadvantages. 5 7…”
Section: Introductionmentioning
confidence: 99%
“…It is a medium sized angiosperm which grows to a height of about 7 to 8 (up to 15 m), more, usually a shrub of 2 to 3 m, many-stemmed forming dumps of gnarled branches (Arbonnier, 2004). N. laevis is widely used in African folk medicine for the treatment of malaria and fever, stomach ache, coughs, sexually transmitted disease, tooth ache, breast cancer, and constipation (Iwu, 2000;Gorman et al, 2003;Eyong et al, 2005). In south eastern and part of the Midwestern Nigeria, the plant is used for the treatment of septic wounds, the young leaves are crushed in little places in water and the extract is put into the eye to cure eye inflammation and redness, it is also administered to stop vaginal bleeding in threatened abortion (Gill, 1992;Kargbo, 1982).…”
Section: Introductionmentioning
confidence: 99%